World trigger. 8 - Ashihara, Daisuke, 1981-; Olsen, Lillian (San Francisco, CA : VIZ Media, LLC, 2016)
"It's a race against time as the ultimate showdowns begin. When a Humanoid Neighbor with a Black Trigger infiltrates the base, A and B-Rank agents take up arms in a battle of numbers vs. power. Meanwhile, it's youth vs. experience with Yuma forces to hold his own against the invaders' most seasoned fighter. Jin's prediction grows ever closer as the battle rages on!"--Back cover.
Translated from the Japanese.
Translation of: Warudo toriga.
"First published in Japan 2013 by Shueisha Inc., Tokyo"--Page facing t.p.
"This book reads from right to left"--Back cover.
"Parental advisory: World Trigger is rated T for Teen and is recommended for ages 13 and up. This v. contains fantasy violence"--Page facing t.p.
Young Adult
Keywords: Human-alien encounters -- Comic books, strips, etc. -- Fiction; Imaginary wars and battles -- Comic books, strips, etc. -- Fiction; Space warfare -- Comic books, strips, etc. -- Fiction; Science fiction comics; Graphic novels